Abundances of Uranium and Thorium Elements in Earth Estimated by Geoneutrino Spectroscopy. Issue 16 (16th August 2022) - Abe, S.; Asami, S.; Eizuka, M.; Futagi, S.; Gando, A.; Gando, Y.; Gima, T.; Goto, A.; Hachiya, T.; Hata, K.; Hosokawa, K.; Ichimura, K.; et al.
Abstract: The decay of the primordial isotopes 238 U, 235 U, 232 Th, and 40 K has contributed to the terrestrial heat budget throughout the Earth's history. Hence, the individual abundance of those isotopes are key parameters in reconstructing contemporary Earth models. The geoneutrinos produced by the radioactive decays of uranium and thorium have been observed with the Kamioka Liquid‐Scintillator Antineutrino Detector (KamLAND). Those measurements have been improved with more than 18‐year observation time, and improvement in detector background levels mainly with an 8‐year nearly reactor‐free period, which now permit spectroscopy with geoneutrinos. Our results yield the first constraint on both uranium and thorium heat contributions. The KamLAND result is consistent with geochemical estimations based on elemental abundances of chondritic meteorites and mantle peridotites. The High‐Q model is disfavored at 99.76% C.L. and a fully radiogenic model is excluded at 5.2 σ assuming a homogeneous heat producing element distribution in the mantle. Plain Language Summary: The energy to drive the Earth's engine comes from two different sources: primordial and radiogenic. Primordial energy comes from the added heat by collisions of accreting material and less so by the energy accompanying the sinking of metal to form the core. The radioactive decays of heat producing elements (i.e., potassium, thorium, and uranium) also generate energy and some of these decaying elements produce antineutrinos (geoneutrinos). Geoneutrino measurements provide the Earth's fuel gauge for its radiogenic power supply and insights into the planet's cooling history. The measurement accuracy of the KamLAND experiment has been improved by an 18‐year long‐term observation and a reduction of the significant background generated by commercial reactors. Consequently, modern geoneutrino measurements have entered an era of distinct spectroscopic contributions coming from uranium and thorium. The KamLAND result is consistent with compositional models for the bulk silicate Earth (the crust plus the mantle) predicting low to medium radiogenic heat (10–20 TW (10 12 W)) and disfavor high concentration models (30 TW). This constraint sets the best limit on the permissible radiogenic energy budget in the Earth. Geoneutrino observations now begin to make significant contributions to the understanding of fundamental driving forces powering the Earth dynamic behavior. Key Points: Geoneutrino measurement with low reactor neutrino backgrounds improves the distinct spectroscopic contributions of U and Th Radiogenic power in the Earth estimated from this geoneutrino measurement is consistent with a range of models and disfavors the higher power model Identifying the Earth's mantle contribution to the total geoneutrino flux strongly depends on an accurate estimation of the crustal contribution